Proteomic analysis of aqueous humor from patients with myopia - Duan, Xiaoming (Molecular Vision, 2008)
PURPOSE: The mechanism of axial elongation in the myopic eyeball remains to be elucidated. It is known that the expression profile for some proteins in the aqueous humor (AH) changes in some diseases. Accordingly, determinations of these AH proteins may serve to understand their potential role in this pathogenesis. To identify the possible mechanism in myopia development, a proteomic analysis of the AH composition from high myopic eyes (patients) was performed and compared with that of the AH composition from non-myopic cataract eyes (controls). METHODS: Total protein concentration in AH was determined by the Bradford method, and separation profiles were analyzed by two-dimensional (2D) gel electrophoresis. Protein in gel was determined by silver stain, and the separation profiles were analyzed to assess spot density changes between myopia and non-myopia patients. These spots in gel were isolated and identified by mass spectrometry. RESULTS: The total protein concentration in AH with high myopia was significantly greater than that of non-myopia. A total of six spots were significantly increased in 2D gels from high myopia. The spots were derived from albumin, transthyretin, and a vitamin D-binding protein. CONCLUSIONS: The protein composition in AH was significantly different between myopia and non-myopia. The identified proteins could be a potential biomarker for high myopia development and may play a role in the mechanisms of myopia ocular axial elongation.